2016
DOI: 10.1097/hjh.0000000000000871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diuretics on sodium-dependent glucose cotransporter 2 inhibitor-induced changes in blood pressure in obese rats suffering from the metabolic syndrome

Abstract: These data suggest that a SGLT2 inhibitor elicits its beneficial effects on glucose metabolism and hypertension in study participants with metabolic syndrome undergoing treatment with diuretics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 43 publications
1
37
0
1
Order By: Relevance
“…In addition, SGLT2 inhibitors can potentially reduce SNS activity that is augmented in part due to hyperglycemia [41, 48], although empagliflozin did not affect SNS activity in younger patients with type 1 diabetes [46]. More recently, some experimental studies showed that SGLT2 treatment could improve circadian rhythm and lability of BP, indicating a possible major cardioprotective role for this class of drugs [49–51]. In the EMPA-REG OUTCOME trial, empagliflozin treatment has elicited marked risk reduction for CV mortality and hospitalization as a result of worsening heart failure in patients with T2DM and established CVD [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SGLT2 inhibitors can potentially reduce SNS activity that is augmented in part due to hyperglycemia [41, 48], although empagliflozin did not affect SNS activity in younger patients with type 1 diabetes [46]. More recently, some experimental studies showed that SGLT2 treatment could improve circadian rhythm and lability of BP, indicating a possible major cardioprotective role for this class of drugs [49–51]. In the EMPA-REG OUTCOME trial, empagliflozin treatment has elicited marked risk reduction for CV mortality and hospitalization as a result of worsening heart failure in patients with T2DM and established CVD [10].…”
Section: Discussionmentioning
confidence: 99%
“…A recent phase III study and a meta‐analysis have shown that SGLT2i significantly reduce 24‐hour ambulatory BP, with significant reductions in both daytime and nighttime BP . Other recent studies have demonstrated that administration of the SGLT2i empagliflozin can change the circadian rhythm of BP from a nondipper to a dipper profile in salt‐treated, obese Otsuka Long Evans Tokushima Fatty (OLETF) rats and likewise with luseogliflozin administered to SHR/NDmcr‐cp (+/+) rats, a model of metabolic syndrome . Similarly, in human studies BP reduction by an SGLT2 inhibitor has been shown to be associated with the restoration of a disrupted circadian rhythm of BP from a nondipper to a dipper pattern in hypertensive subjects with impaired glucose metabolism and insulin resistance …”
mentioning
confidence: 99%
“…This is the hypothesis tested by Rahman et al as reported in this issue of the Journal of Hypertension. In a rat model of the metabolic syndrome, the spontaneously hypertensive/ NIH-corpulent rat (SHRcp) rat, they report very promising reductions in both blood glucose and blood pressure by the SGLT2 inhibitor luseogliflozin (L), especially in combination with the diuretics furosemide plus hydrochlorothiazide (D) [7]. Of course, the question is: at what cost are these benefits gained?…”
mentioning
confidence: 99%
“…Rahman et al performed meticulous balance studies for sodium, potassium and chloride over the whole course of their study [7]. Despite the increase in body weight net sodium and potassium balance fell over the entire period reaching levels just above zero for the L þ D by week 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation